Self-assembled polyelectrolytes with ion-separation accelerating channels for highly stable Zn-ion batteries - Hu, Xueying; Dong, Haobo; Gao, Nan; Wang, Tianlei; He, Hongzhen; Gao, Xuan; Dai, Yuhang; Liu, Yiyang; Brett, Dan J. L.; Parkin, Ivan P.; He, Guanjie (Nature communications, 2025)
Aqueous zinc-ion batteries offer a sustainable alternative to lithium-ion batteries due to their abundance, safety, and eco-friendliness. However, challenges like hydrogen evolution and uncontrolled diffusion of H⁺, Zn²⁺, and SO₄²⁻ in the electrolyte lead to the dendrite formation, side reactions, and reduced Coulombic efficiency for Zn nucleation. Here, to simultaneously regulate the diffusion of cations and anions in the electrolyte, an ion-separation accelerating channel is constructed by introducing layer-by-layer self-assembly of a flocculant poly(allylamine hydrochloride) and its tautomer poly(acrylic acid). The dual-ion channels, created by strong electrostatic interactions between carboxylate anions and ammonia cations, block SO 4 2 − and promote the uniform Zn deposition along the Zn(002) plane, exhibiting a CE of 99.8% after 1600 cycles in the Cu||Zn cell. With the facile fabrication of the layer-by-layer self-assembled Zn anode, an Ah-level pouch cell (17.36 Ah) with a high mass loading (> 8 mg cm⁻²) demonstrates the practical viability for large-scale applications, retaining a capacity of 93.6% for 250 cycles at 1.7 C (35.3 min). This work enables more uniform Zn deposition and enhances the cycling stability in larger pouch cells, paving the way for the commercialisation of zinc-ion batteries. The use of aqueous Zn-ion batteries is hindered by parasitic reactions, dendrite formation, and low Coulombic efficiency of Zn metal electrode. Here, authors regulate the electrolyte ions diffusion via ion-separation accelerating channel through self-assembly of poly(allylamine hydrochloride) and poly(acrylic acid).